Sistem Manajemen Parkir Berbasis Web dengan QR Code dan Notifikasi Real-Time - Ramdani, Nico; Ridwansyah, Ridwansyah; Wasid, Asep; Irawan, Debi (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
The growth in the number of vehicles in the university environment requires a more efficient, secure, and integrated parking management system. Conventional parking systems that still rely on manual recording cause various problems, such as long queues, delays in data validation, low information accuracy, and a high potential for vehicle loss. This study aims to develop a WebBased Parking Management System with the application of QR Codes as digital vehicle identities and real-time notifications to monitor vehicle entry and exit activities. The system is built using Node.js as the backend, with the support of responsive web technology and a multi-role architecture consisting of administrators, officers, and students. Key features include QR Code scanning, automatic parking transaction recording, real-time monitoring dashboard, and sending notifications to users regarding parking status. The system development method uses a prototype approach, enabling continuous interaction between developers and users in feature refinement. Testing results show that the system can improve parking operational efficiency, minimize recording errors, and enhance vehicle security through a digital verification process. Thus, this system can be an adaptive smart parking solution for the campus environment in supporting digital transformation and improving parking services.